ANALISIS WORK BEHAVIOR TERHADAP CUSTOMER ATTITUDE MELALUI STATE OF THE WORKING ENVIRONMENT DI FORTIS CAFE SIDOARJO - Nilma Firda Nur Fidia; Khafid khoirul hanafi; Hilda Putri Wulandari; Ayu Lucy Larassaty (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
Employee work behavior is greatly affected by various kinds of customer attitudes and actions, both positive and negative. In general, the positive attitude of the customer will indirectly encourage performance improvement. This study aims to analyze how employees work behavior towards various customer attitudes both positively and negatively. This research method uses qualitative methods. The population of this study are employees at PT Jack Solusi Indonesia with a total of 42 employees. The collection technique in this study was to conduct interviews with cafe managers and employees. The data obtained is based on information from the management and various existing literature. The results of this study refer to how much customer behavior influences how employees work. Employees carry out their duties and obligations according to the direction of the manager. Of course, every direction that has been given has not gone well due to the attitude of customers in the work environment. Similarly, partially alias the tone of a significant influence between work behavior and customer attitudes in the work environment..